Chinese teachers' perceptions of the 'good citizen': A personally-responsible citizen. Issue 1 (2nd January 2017) - Li, Hui; Tan, Chuanbao
Abstract: Conceptions of the 'good citizen' have implications for defining the goals of civic education and formulating civic education programs. In Mainland China, the concept of 'good citizen' is clearly defined by the authorities in the official curriculum guidelines. Teachers' perceptions of a 'good citizen', however, may differ from any official definition and will influence their approaches to the implementation of civic education in schools. The research reported here used qualitative methods to explore some Chinese junior high school teachers' perceptions of a 'good citizen', drawing on Westheimer and Kahne's identification of three 'visions of citizenship' used in the US as a baseline. We argue that an effective civic education curriculum must consider teachers' actual perceptions of a 'good citizen' in practice and that Chinese teachers' awareness and understanding of citizenship needs to improve.